THE RATIO OF UROLOGISTS FOR EACH REGENCY AND CITY IN EAST JAVA INDONESIA AND THE INDICATORS AFFECTING THEIR DISTRIBUTION - Wirjopranoto, Soetojo; Surya, Prima Ardiansah; Jamhari, Moh. Arif Hakim; Azmi, Yufi Aulia; Ash-Siddiq, Muh. Abdurrahman Rasyid; Muharram, Farizal Risky (Indonesian Urological Association, 2025)
Objective: Research on the distribution of urology in Indonesia, especially in East Java, has not been widely discussed. There are still several areas in East Java that do not have a urologist at all. We try to find out the factors underlying this distribution through several indicators. Material & Methods: Data from all hospitals in East Java were compiled with data of urologists in East Java obtained from the Indonesian Urological Association, supplemented by information from social media and the telephone of the hospital operator. The number of urologists and hospitals with urology services is then correlated with the human development index, the education index, purchasing power index, health index, and regional minimum wage. Results: The ratio of urologists in each district and city in East Java is not evenly distributed, and likewise with the hospitals that provide urology services in each district and city in East Java. The ratio of urologists and the number of hospitals providing urology services are significantly related to the human development index, the education index, the purchasing power index, the health index, and the regional minimum wage. Conclusion: The location of a urologist's practice is related to the development of an area, which in this study is assessed through indicators of human development, education, health, and economy. Keywords: Urologist Ratio, East Java, Urology.